Perancangan Prototype Aplikasi Review Produk dan Jasa Berbassis Web - Anranur Uwaisy Marchiningrum; Budiawan, Reza; Satria Praditha, Villy; Harry Prayogo, Ario (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Reviewing goods and services is an activity carried out to help provide information between users or reviewers about goods and services. However, in Indonesia there is still little attention and lack of interest in review activities, so that information about goods and services is still difficult to obtain. The solution provided is to create a web-based application that can help provide information about goods and services. This study designs a prototype of a web-based goods and services review application. This application provides various review information about goods and services. The creation of this application will be divided into several modules, such as the admin module, reviewer module, sponsor module, basic module and social network. The admin module is a module that contains data management carried out by the admin and the settings contained in this application. Meanwhile, the reviewer module explains the features that will be used by users. The sponsor module contains features that can be used by the sponsor. In addition, there are basic modules and social networks that function as communication links between users. This application uses the SDLC (Systems Development Lifecycle) method with a waterfall model and is made using the codeigniter framework.